Association between Klotho levels in cerebrospinal fluid and choroid plexus enlargement in neurodegeneration - Sacchi, Luca; Arcaro, Marina; Bocca, Giorgio; Schmid, Lia; Carandini, Tiziana; Ghezzi, Laura; Pintus, Manuela; Pietroboni, Anna Margherita; Fenoglio, Chiara; Serpente, Maria; Conte, Giorgio; Triulzi, Fabio; et al. (Frontiers in aging neuroscience, 2025)
Background: Klotho is a longevity-associated protein found in membrane-bound and secreted forms, with the latter detectable in blood and cerebrospinal fluid (CSF). Circulating Klotho mainly originates from the kidney, while the choroid plexus (CP) secretes it into the CSF. CP dysfunction is associated with reduced Klotho expression and neurodegeneration and may result in CP enlargement on magnetic resonance imaging (MRI). In this preliminary study, we investigated Klotho levels in neurodegenerative patients and their association with CP enlargement. Materials and methods: We retrospectively analyzed 40 patients from the IRCCS Ca′ Granda Ospedale Policlinico, Milan, including 32 neurodegenerative patients (Deg) and 8 cognitively normal controls (NonDeg). CSF and serum Klotho levels were measured using an ELISA kit. KL-VS and apolipoprotein E (APOE) genotyping were performed. CP volumes were segmented using ITK-SNAP and normalized to total intracranial volume (TIV), resulting in a measure known as the CP volume fraction (CPVF). A multivariate linear regression analysis was conducted, adjusting for diagnostic group, age, sex, APOEε4, CPVF, and gray matter volume fraction (GMVF). Results: CSF Klotho levels were significantly lower in Deg patients (mean = 729 pg./mL, SD = 364) compared to NonDeg individuals (mean = 1,077 pg./mL, SD = 220) (t = 3.44, p = 0.003). Higher CPVF (β = −0.34, 95% CI [−0.64, −0.05], p = 0.023) was independently associated with lower CSF Klotho levels. Conclusion: In this preliminary study, we observed a strong association between CSF Klotho levels and CP enlargement. Reduced CSF Klotho levels, due to CP dysfunction, may contribute to neurodegeneration. If confirmed in larger cohorts, this association suggests that CSF Klotho may serve as a biomarker for CP enlargement, possibly reflecting its underlying dysfunction.
Veröffentlicht: 27. November 2025
Gesehen am 25.02.2026